Conserving the endangered Black-throated Finch southern subspecies: what do we need to know?. (2nd October 2019) - Mula Laguna, Juan; Reside, April E.; Kutt, Alex; Grice, Anthony C.; Buosi, Peter; Vanderduys, Eric P.; Taylor, Martin; Schwarzkopf, Lin
ABSTRACT: Successful conservation of threatened species requires judicious allocation of limited resources. The threatened Black-throated Finch southern subspecies ( Poephila cincta cincta ), endemic to north-eastern Australia, has suffered an 80% contraction in its historical range. Stemming ongoing habitat loss is the main priority in its conservation, but remaining areas where habitat has been degraded require active management. However, the scarce information about the subspecies' ecology has inhibited effective conservation planning. In this paper, we gather and review current knowledge on the Black-throated Finch southern subspecies' ecology and threats and propose a list of research priorities aimed to support conservation management. We highlight how available knowledge could lead to false assumptions due to the limited temporal scope of most studies and their focus on a substantially modified area within its current range. There is a shortage of information on the present population size and distribution of the subspecies, which creates uncertainty about its conservation status. Our top three priority actions are focused on monitoring the remaining populations and evaluating the effects of management practices in pastoral land. We expect this paper to serve as a first step to create a cohesive framework for researchers and stakeholders when deciding to invest in the conservation of this iconic finch.